A Supramolecular Investigation on the Interactions between Ethyl terminated Bis–viologen Derivatives with Sulfonato Calix[4]arenes. Issue 3 (30th January 2017) - Madasamy, Kanagaraj; Gopi, Sivalingam; Kumaran, Marimuthu Senthil; Radhakrishnan, Srinivasan; Velayutham, David; Mareeswaran, Paulpandian Muthu; Kathiresan, Murugavel
Abstract: Herein, we report the synthesis and guest‐host complexation between isomeric xylylene interconnected ethyl terminated bis‐viologens (EDV) with p ‐sulfonatocalix[4]arene (SC4 A). Guest‐host interactions betweenEDV and SC4 A were monitored by CV (cyclic voltammetry), 1 H and DOSY (Diffusion Ordered Spectroscopy) NMR titrations. CV titrations showed a partial inclusion complex formation betweenEDV and SC4 A which is further confirmed by 1 H NMR and DOSY titrations. It is evident from 1 H NMR titrations that all the three isomers ofEDV forms a stable inclusion complex with SC4 A where SC4 A caps the terminal. o ‐ and m ‐ isomers ofEDV interacts differently than their corresponding p ‐isomer. 1 H NMR titration reveals that o ‐ and m ‐xylylene units are incorporated into the SC4 A cavity whereas p ‐xylylene unit is only partially included into the cavity during the interaction. Further, it is observed that the ethyl terminated viologen adopts axial orientation in concordance with previous reports. DOSY measurements further confirmed the formation of inclusion complex between the bis‐viologen and SC4 A and indicated the formation of aggregates at higher concentrations of SC4 A. Results clearly indicate that the bis‐viologens possess multiple binding sites for the multivalent SC4 A host and based on the concentration of SC4 A, several types of interactions exists between the two predicting a complex binding model. Abstract : Guest‐host interactions between synthesized isomeric xylylene interconnected ethyl terminated bis viologensEDV and p ‐sulfonatocalix[4]arene SC4 A were carried out and monitored by CV (cyclic voltammetry), 1 H and DOSY (Diffusion Ordered Spectroscopy) NMR titrations. It is evident from 1 H NMR titrations that all the three isomers ofEDV forms a stable inclusion complex with SC4 A where SC4 A caps the terminal. DOSY measurements further confirmed the formation of inclusion complex and aggregates between the bis‐viologens and SC4 A at higher concentrations of SC4 A.